1991
DOI: 10.1111/j.1365-2796.1991.tb00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of cirrhosis undiagnosed during life: a comparative analysis of 73 undiagnosed cases and 149 diagnosed cases of cirrhosis, detected in 4929 consecutive autopsies

Abstract: In 4929 consecutive autopsies performed during a period of 4 years, 222 cases (4.5%) of cirrhosis were found, of which 149 (3%) were detected while the patients were alive (diagnosed cirrhosis) and 73 (1.5%) were not detected while the patients were living (undiagnosed cirrhosis). Fifty-three of the 73 undiagnosed patients appeared to be completely without signs of cirrhosis (silent cirrhosis). In the diagnosed group, 70% of patients died from hepatic causes, in contrast to 16% in the undiagnosed group. At aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
12

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 7 publications
3
46
0
12
Order By: Relevance
“…However, the diagnosis of cirrhosis is frequently missed [44], with autopsy studies revealing that up to one third of patients are not identified during their lifetime [45]. Thus, segregating patients with mild or no fibrosis, and hence little chance of liver-related adverse outcomes, from those with more advanced disease or in fact cirrhosis, is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnosis of cirrhosis is frequently missed [44], with autopsy studies revealing that up to one third of patients are not identified during their lifetime [45]. Thus, segregating patients with mild or no fibrosis, and hence little chance of liver-related adverse outcomes, from those with more advanced disease or in fact cirrhosis, is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, cirrhosis is a common disease, which is frequently undiagnosed [4,5] . The risk of biopsy (morbidity 3%, mortality 0.03%) [7] may limit its use in screening for this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic artery (HA) measurements included: diameter (D) in cm, cross-sectional area (AR) in cm 2 , time-averaged mean velocity (V TAM ) in cm/s and blood flow volume (BF) in mL/min. Resistance index (RI) of HA (percentage) was the ratio of 100 × the difference of peak systolic velocity minus end diastolic velocity to peak systolic velocity, automatically given by machine's software.…”
Section: Cdu Technique and Indexesmentioning
confidence: 99%
See 2 more Smart Citations